Strategies in improving teacher motivation madrasah tsanawiyah negeri 2 muara enim - Widyawati Widyawati; Hardiyansyah Hardiyansyah; Nisma Aprini (Journal of Indonesian Management, 2023)
Strategy in Improving Teacher Work Motivation Madrasah Tsanawiyah Negeri 2 Muara Enim. The author conducted research with the aim of analyzing the Strategy in Improving Teacher Work Motivation of Madrasah Tsanawiyah Negeri 2 Muara Enim. This type of research is a form of field research using a qualitative approach, which is a research approach that produces descriptive data in the form of written or spoken words from objects or subjects that are observed and then drawn conclusions. Researchers try to understand the phenomena experienced by research subjects and conduct studies of field studies. Qualitative research is also a form of research that aims to describe existing problems that occur in the object of research. The results of the study found that Madrasah Tsanawiyah Negeri 2 Muara Enim with the position of the school must be able to capture opportunities by maximizing its strengths. The strategy in the SO strategy can be done by maximizing the strategic location, maximizing promotion, having a majority of teaching staff with degrees in accordance with competence is an opportunity to add value to promotion, teachers have high motivation, making opportunities in improving competence and establishing good relations with school residents, being an opportunity to establish communication with committees and communities.